Pasti spletne pornografije in pasti raziskovanja pornografije - Erzar, Tomaž (Bogoslovni vestnik, 2023)
In this article, we present some of the problems of defining, measuring, interpreting, and citing the effects that viewing internet pornography and on-line sexuality have on different populations in today’s broadband-connected world. We describe numerous negative consequences of this behavior and related problems in personal and interpersonal functioning. Follows a methodological and substantive analysis of eight often cited studies which are said to confirm the positive effects of pornography. The results of the analysis show that only one study, which summarizes the opinions and behavior of a part of the younger, self- -selected student population, fits this description, while most of the other studies confirm the opposite effects. The results are interpreted in the light of understanding the internet pornography use as a process that begins with accepting deceptive presentation of sexuality and often ends with addiction.
Keywords: addiction; deception; definicija; definition; internet pornography; methodology; metodologija; negative effects; negativni učinki; positive effects; pozitivni učinki; spletna pornografija; zasvojenost; zavajanje